Assessment of the body composition of brazilian boys: the bioimpedence method - Martim Bottaro; Adroaldo C. de Araujo Gaya; Claudio Roberto Escovar Paiva; Ricardo Flávio de Araújo Bezerra (Universidade Federal de Santa Catarina, 2002)
The purpose of this study was to determine the applicability and predictive accuracy of previously published total-body resistance Bioimpedence (BIA) equations for estimation of body composition of 29 Brazilian boys (10 to 14 years old). A DXA (DPX-IQ, Version 4.6 A) was used to obtain reference measures of relative body fat (%BF) and fat free-mass (FFM). Total-body resistance was measured with a Biodynamics Ò (Model-310) analyzer. The BI equations published by Houtkooper et al. (1992), Jenkins et al. (1999), and Yonamine & Pires Neto (2000 - equations B2, B3 and B4 used) were cross-validated. The results were as follows: validity coeffi cients (r) from the Biodynamics ranged from 0.87 (B3 Yonamine equation) to 0.98 (Houtkooper equation); prediction errors (SEE and E) ranged from 1.88 kg (Jenkins) to 3.66 kg (B3 Yonamine). The Houtkooper and Jenkins equations accurately estimated average FFM with an acceptable prediction error (SEE = 1.97 and 1.88 kg, respectively). The B2, B3 and B4 Yonamine equations signifi cantly overestimated average FFM by 27.33 kg ; 10.77 kg and 1.97 kg, respectively. Based on these results, we recommend using the Jenkins et al. (1999) equation, or the Houtkooper et al. (1992) equation for estimating the body composition of young, healthy, Brazilian boys. RESUMO O objetivo deste estudo foi o de determinar a aplicabilidade e a precisão de equações de Bioimpedância (BIA) previamente publicadas na avaliação da composição corporal de 29 meninos brasileiros (10 a 14 anos). O DXA (DPX-IQ, Versão 4,6 A) foi usado na obtenção da gordura relativa (%G) e da massa corporal magra (MCM) de referência. A resistência corporal total foi medida com o analisador Biodynamics â (Modelo - 310). Foram analisadas as equações de Houtkooper et al. (1992), Jenkins et al. (1999), e as equações B2, B3 e B4 de Yonamine & Pires Neto (2000). Os resultados encontrados foram: o coefi ciente de validade (r) do Biodynamics variou de 0,87 (B3/Yonamine) a 0,98 (Houtkooper); o erro de estimativa padrão (EPE) e o erro total (E) variaram de 1,88kg (Jenkins) a 3,66kg (B3/Yonamine). A equação de Houtkooper e a de Jenkins forneceram estimativas aceitáveis tanto da média da MLG quanto do EPE (1,97 e 1,88kg, respectivamente). As equações B2, B3 e B4 superestimaram de forma signifi cativa a MCM (EC = -27,33kg; EC = -10,77kg; e EC = -1,97kg, respectivamente). Baseados nesses resultados é recomendável o uso da equação de Jenkins et al. (1999) ou a de Houtkooper et al. (1992) na estimativa da composição corporal de meninos brasileiros jovens e sadios da presente amostra.